A RESEARCH ON EXAMİNİNG THE FACTORS AFFECTİNG STUDENTS' MOBİLE BANKİNG USAGE (Third Sector Social Economic Review, 2024)
Mobile banking services offer significant advantages over traditional banking methods by allowing users to carry out their financial transactions easily and at any time. The study investigates the factors influencing mobile banking adoption among Ardahan University students using the Technology Acceptance Model (TAM). The analysis of data from 336 participants revealed that behavioral intention was the most influential factor, while subjective norm had the least impact. The study also found that trust significantly affected behavioral intention, the dependent variable in TAM. However, self-efficacy, subjective norm, perceived usefulness, and perceived ease of use did not predict behavioral intention. The research highlights the importance of trust in technology adoption among young users and provides valuable insights for understanding mobile banking usage. The study's limitations and suggestions for future research are also discussed, emphasizing the need for further exploration of mobile banking adoption across different age groups and using various technology acceptance models. The findings suggest that banks should prioritize building trust and enhancing the user experience to encourage mobile banking adoption among young adults. Moreover, the research underscores the importance of tailoring marketing strategies and security measures to the specific needs and preferences of this demographic.
Keywords: Information and Communication Technologies; Technology Acceptance Model (TAM); Mobile Banking; Trust; Behavioral Intention